2018
DOI: 10.1186/s13756-018-0323-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance of bacteria isolated from the cerebrospinal fluid of neurosurgical patients at Peking Union Medical College Hospital

Abstract: BackgroundPostoperative central nervous system infections (PCNSIs) represent a serious complication, and the timely use of antibiotics guided by the identification of the causative pathogens and their antibiotic sensitivities is essential for treatment. However, there are little data regarding the prevalence of PCNSI pathogens in China. The aim of this study is to investigate the features of pathogens in patients with PCNSIs, which could help clinicians to choose the appropriate empirical antibiotic therapy.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 33 publications
17
25
2
Order By: Relevance
“…Our study demonstrated Gram-positive bacteria was the most common organism, accounting for approximately 56% of the total isolates. This result was consistent with previous studies [12,18,19]. On the contrary, Aishwarya et al from India reported the proportion of Gram-negative bacteria causing PCNSIs was even as high as 91.6% [20].…”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated Gram-positive bacteria was the most common organism, accounting for approximately 56% of the total isolates. This result was consistent with previous studies [12,18,19]. On the contrary, Aishwarya et al from India reported the proportion of Gram-negative bacteria causing PCNSIs was even as high as 91.6% [20].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that gram-positive bacteria were main infectious bacteria after intracranial surgery, which was consistent with that in the literatures [8,9]. Our study proved that coagulase-negative staphylococcus (CNS) were the most common bacteria, accounting for 41.6% of all infection pathogens, followed by 3.2% of Streptococcus viride and 3.2% of Staphylococcus aureus.…”
Section: Discussionsupporting
confidence: 92%
“…PCNSIs caused by AB are still a serious but rare condition. In the present research, the morbidity was approximately 0.17% and accounted for 44.4% of the gram-negative organisms (7), which was similar to the findings of previous studies (22). The mortality was reported to be over 30% in some previous studies and even over 70% when the isolates were resistant to carbapenems (8), which are higher rates than that found in our study (25%).…”
Section: Discussionsupporting
confidence: 90%
“…These findings may be related to the following three points. First, approximately half of the neurosurgery operations at our hospital involved the endonasal transsphenoidal approach, and the percentage involving PCNSIs was also nearly 50%, as previously reported (7). Second, CSF rhinorrhea, a complication of the surgery, is an important risk factor in PCNSIs (10).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation